Analysis Of Customer Satisfaction On Thrift Purchasing Decisions In Students Of Polytechnic LP3I - Surbakti, Eka Wulandari; Rachmawati, Yeni; Nurlela; Amalia, Putri (Cattleya Darmaya Fortuna, 2023)
The development of social media has resulted in changes in the development of fashion trends among society, especially students. One of them is thrift products or used clothes which are often used as a solution for students who want to still look stylish (fashionable) with well-known brands but at affordable and cheap prices. In this case, consumer satisfaction plays an important role in purchasing decisions. The purchasing decision process is an action of consumer behavior that will give rise to positive and negative responses to the product to be purchased. If the level of consumer satisfaction shows positive, the consumer will decide to buy the product again. This research aims to find out how much influence the level of consumer satisfaction has on thrift purchasing decisions among LP3I Medan Polytechnic Students. The data collection technique uses quantitative methods with a simple linear regression approach and a sample of 60 respondents. The research results show that partially, consumer satisfaction influences purchasing decisions (at a significant value of 0.000 < 0.05 with a calculated t of 10.421 > 1.672 greater than the t table value) so it can be concluded that H0 is rejected and H1 is accepted, which means there is an influence on satisfaction consumers (X) on purchasing decisions (Y). Judging from the coefficient of determination, the level of consumer satisfaction has an effect of 0.652, which shows that the Consumer Satisfaction variable has an effect of 65.2% on purchasing decisions, while the rest is influenced by other variables outside this research